Between Shame and Femininity: The Experience of Lithuanian Women Who Have Left the Industry of Prostitution. Ethnographic Field Research - Kondrataitė, Irma (Socialinė teorija, empirija, politika ir praktika, 2021)
This paper focuses on women who have left the industry of prostitution and is based on ethnographic field studies conducted in several cities in Lithuania. Four women have agreed to share their stories of entering and leaving the industry of prostitution and in all their narratives the core accent was the experience of shame. During the interviews, each of these women had an urge to express the importance of moral virtues in their lives and, as all of them claimed, they felt ashamed because “they have lost their femininity.” It was very important for these women to emphasize that they are not “easy going” or “loose women,” but women who have high moral standards and that entering the industry of prostitution was never the idea of their own, it was rather the consequence of several different factors varying from manipulations of their pimps to their poor social and financial circumstances. It is evident that these 4 women understand femininity as opposed to the work which women in prostitution do (providing sexual service). According to their narratives, women in prostitution, due to the aspect of providing sexual service to many male clients, lose the virtue of femininity, and that is the main factor generating the experience of shame. Due to experience of shame, all these women could not share their traumatic experiences with their families or even close friends. The construction of femininity in Lithuania is heavily influenced by the cult of Mother Mary and the doctrine of innocence. Therefore, the division of women into the categories of the Madonna and the Whore is still very much prominent in the Lithuanian society today. According to the Code of Administrative Offenses, prostitution in Lithuania is categorised as a crime against morality, and both the client and the sexual service provider must be fined. Nevertheless, the data shows that disproportionately very few clients get punished compared to the sexual service providers, mainly women. While non-governmental organisations are putting their efforts to focus the attention of society and the law institutions onto the client and in that way to put an end to the stigmatisation of women in the industry of prostitution, since both the client and the provider of sexual services are needed for the act of prostitution, in reality no social rehabilitation programs in social politics exist for these women in Lithuania today, apart from the help they receive from non-governmental organisations. Therefore, they are left to cope with the traumatic experience on their own, while the stigmatisation of women in prostitutions persists. Empirical material confirms the hypothesis that the experience of shame, which is based on the construction of femininity and the system of moral virtues in the society, reflected in the law defining prostitution in Lithuania, creates certain psychological and social configuration. Due to this configuration, these particular women experience social isolation. Therefore, their rehabilitation from the trauma period is prolonged and new obstacles in achieving well-being in their lives emerge.